Reshaping Chinese Cities. Neoliberal Transition, Embedded Contestation, and Urban Renewal of Lanzhou. - Guo, Jie (LIT, 2020)
This book examines speculative urban development and new pattern of urban governance in the context of China's neoliberal turning. By adopting a post-structuralist lens, the book discusses the restless interactions and power relations, hidden behind the restless conflicts, struggles, negotiations and cooperation among multiple stakeholders during state-led and capital-driven land development. This book therefore reveals a state-led benefit distribution mechanism through which stakeholders are actively and passively involved in the renewal process and slowly promote speculative land development projects in continued cooperation and competition.
Keywords: Stadterneuerung; Stadtraum; Transformation; Flächenentwicklung; Urban Governance; Gewerbegebiet; Industriegebiet; Flächenbewirtschaftung; Interessenkonflikt; Entscheidungsfindung; Stadtpolitik; Neoliberalismus